PEMBINAAN USAHA KERAJINAN LUKISAN KACA DI DESA NAGASEPAHA - Luh Kartika Ningsih; Putu Adi Kerta Permana Putra; Kadek Agus Ariwibawa (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2023)
The problem experienced by glass painting craftsmen is the lack of production and marketing in glass painting craft products in Nagasepaha Village. So far, glass painting craftsmen produce and market this limited glass painting due to the limited tools they have and the lack of good marketing, so the craftsmen need a long time to produce and market this glass painting. For these problems, it is advisable to use more modern tools and provide counseling about marketing management or internet marketing. The method used is to provide an introduction to more modern tools so that craftsmen can complete training glass paintings faster, counseling about how to market through social media. The result of this activity is that this glass painting craftsman is able to increase production capacity and wider marketing through social media. Through increasing production capacity, it will certainly provide an opportunity to increase the income of glass painting craftsmen. During this community service activity, the craftsmen gave a good welcome, so that this activity could be carried out properly.